2011
DOI: 10.1002/pssb.201147113
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic ordering and electronic properties of Pd‐doped ZnO

Abstract: We carried out first-principles spin-polarized calculations in order to provide comprehensive information regarding the structural, electronic and magnetic properties of the Pd x Zn 1-x O (with x ¼ 0.0625) semiconductor. The highly accurate allelectron full-potential linearized augmented plane wave method was used to calculate total energy and electronic structure of the Pd-doped ZnO semiconductor. The recently developed Wu-Cohen generalized gradient approximation to the exchange correlation functional was ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Only diffraction peaks from ZnO (nor palladium) were detected. The palladium ionic radius (0.80 Å) is close in size to that of Zn 2+ (0.74 Å), indicating the possible substitution of the Zn 2+ positions into the ZnO cell, as has been established by computational calculations for 6.25 Pd mol % into the hexagonal ZnO matrix . At higher Pd content, an octahedral interstitial site into the cell could also be occupied, as mentioned by Hussein .…”
Section: Resultsmentioning
confidence: 99%
“…Only diffraction peaks from ZnO (nor palladium) were detected. The palladium ionic radius (0.80 Å) is close in size to that of Zn 2+ (0.74 Å), indicating the possible substitution of the Zn 2+ positions into the ZnO cell, as has been established by computational calculations for 6.25 Pd mol % into the hexagonal ZnO matrix . At higher Pd content, an octahedral interstitial site into the cell could also be occupied, as mentioned by Hussein .…”
Section: Resultsmentioning
confidence: 99%
“…When each feature of the EIS was characterized by an electrical circuit using software that contains resistance, capacitance, or constant phase elements that are connected in series or parallel to form an equivalent circuit, as shown in Figure 9, then we found that the resistance R 1 was in parallel with the constant phase element CPE 1 , which was responsible for impedance at the Pt/electrolyte interface [36,37]. The CPE distributed element was introduced for dispersive characteristics of the interfacial capacitance [38,39].…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 99%